Bone demineralization promotes superior spread of preosteoblast in culture - Prado Manfredi, Gustavo Goncalves do; Tokuhara, Cintia Kazuko; Salmeron, Samira; Spada de Carvalho, Erika Beatriz; Liboa-Filho, Paulo Noronha [UNESP]; Damante, Carla Andreotti; Passanezi Sant'Ana, Adriana Campos; Ragghianti Zangrando, Mariana Schutzer; Aguiar Greghi, Sebastiao Luis; Rubo de Rezende, Maria Lucia (Wiley-Blackwell, 2019)
Previous studies have shown substances capable of similar effects of demineralization, accelerating the process of bone remodeling. This study investigated preosteoblasts behavior in cell culture after bone demineralization with citric acid and tetracycline. Seventy-four Wistar rats provided 144 calvarial bone samples, 126 of which were randomly divided in seven groups according to the treatment given to the surface: no demineralization (C), citric acid (CA), tetracycline (TCN) during 15, 30, and 60 s. Each group received preosteoblasts cultured for 24, 48, and 72 hr. Eighteen remaining samples were analyzed for the atomic percentage (A%) by energy dispersive spectroscopy (EDS) before and after demineralization. The average percentage of bone area covered by cells increased with time and it was significantly higher after 24 and 48 hr of culture in groups CA15s, CA30s, CA60s, TCN15s, and TCN30s than in groups TCN60 and C (p < 0.05). The cell morphology in all CA and TCN groups was shown to be compatible with more advanced stages of differentiation than in C group. The A% changed after demineralization. We conclude that demineralization with citric acid or tetracycline for 15-30 s increased the area of bone surface covered by preosteoblasts. The A% changes were not sufficient to impair the cells spreading and morphology. Bone demineralization may promote potential benefits in bone regenerative procedures. Highlights Low pH effects did not interfere on cell growth. Bone demineralization favored the preosteoblasts growth. A possible alternative to improve graft consolidation.
Keywords: bone tissue; cell culture; citric acid; osteoblasts; tetracycline